Altered Brain Functional Connectivity in Betel Quid-Dependent Chewers - Huang, Xiaojun; Pu, Weidan; Liu, Haihong; Li, Xinmin; Greenshaw, Andrew J.; Dursun, Serdar M.; Xue, Zhimin; Liu, Zhening (Frontiers in Psychiatry, 2017)
Background: Betel quid (BQ) is a common psychoactive substance worldwide with particularly high usage in many Asian countries. This study aimed to explore the effect of BQ use on functional connectivity by comparing global functional brain networks and their subset between BQ chewers and healthy controls (HCs). Methods: Resting-state functional magnetic resonance imaging (fMRI) was obtained from 24 betel quid dependent (BQD) male chewers and 27 healthy male individuals on a 3.0T scanner. We used independent component analysis (ICA) to determine components that represent the brain’s functional networks and their spatial aspects of functional connectivity. Two sample t-tests were used to identify the functional connectivity differences in each network between these two groups. Results: Seventeen networks were identified by ICA. Nine of them showed connectivity differences between BQD and HCs (two sample t-tests, p < 0.001 uncorrected). We found increased functional connectivity in the orbitofrontal, bilateral fronto-parietal, fronto-temporal, occipital/parietal, fronto-temporal/cerebellum, and temporal/limbic networks, and decreased connectivity in the parietal and medial frontal/anterior cingulate networks in the BQD compared to the HCs. The betel quid dependence scale (BQDS) scores were positively related to the increased functional connectivity in the orbitofrontal (r = 0.39 p = 0.03) while negatively related to the decreased functional connectivity in medial frontal/anterior cingulate networks (r = -0.35 p = 0.02). Discussion: Our findings provide further evidence that BQ chewing may lead to brain functional connectivity changes, which may play a key role in the psychological and physiological effects of BQ.